MUHAMMADIYAH ORGANIZATION'S INFLUENTIAL CONTRIBUTION TO THE ISLAMIZATION OF KNOWLEDGE - Toha Md Saky, Sheikh Abu; Rochim Maksum, Muhammad Nur; Islam, Md Nurul; Azani, Mohammad Zakki (Zawiyah: Jurnal Pemikiran Islam, 2024)
This paper explores Muhammadiyah's significant contributions to the Islamization of knowledge, emphasizing its integration of Islamic principles with contemporary education and societal needs. Key areas of focus include Muhammadiyah’s extensive network of educational institutions, which offer curricula combining religious teachings with modern sciences, fostering a well-rounded education. The organization’s research and scholarly activities have enriched Islamic thought and philosophy, promoting intellectual discourse through various publications and academic journals. Additionally, Muhammadiyah’s social and cultural programs have positively impacted Indonesian society by addressing both material and spiritual needs through community outreach and development projects. The paper also highlights Muhammadiyah’s global influence, serving as a model for integrating Islamic values with modern education. The importance of the Islamization of knowledge is underscored as a means to bridge the gap between traditional Islamic teachings and contemporary knowledge, fostering ethically grounded generations capable of addressing modern challenges. The study concludes with a call for further research and engagement to document Muhammadiyah’s methodologies, successes, and challenges, ensuring its principles and practices continue to benefit future generations.